PELAYANAN PENGURUSAN PERIZINAN DI KANTOR BADAN PELAYANAN TERPADU PERIZINAN DAN PENANAMAN MODAL (BPTP2M) KABUPATEN ROKAN HULU TAHUN 2013 - 2014 - Wansitio, Husnir; Yusri, Ali (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Coherent Ministering body about permit And Regency Capital Instilling Rokan Hulu is SKPD (region peripheral unit of work) new at Rokan Hulu's regency accords Regent Father oral instruction Rokan Hulu office about permit obliging gets to give service that satisfies to society. Condition of coherent Ministering Body office about permit And Regency Capital Instilling Rokan Hulu who constitutes new SKPD one stills in fix process and needs administration settlement.Service publicing to constitute a direct process among ministering provider with society. On society present moment always hopes and waiting when public service will get better and gets appreciation by society. We shall can understand public service that actually, therefore really needs presumably word theory or concept hits public service.Increasing service to society also constitute effort to increase kesejahtraan society. One of community service area is ministering area about permit which constitute Regency Government task Rokan Hulu and in particular coherent Ministering Body Office about permit And Capital Instilling to even out it.Keywords: Pelayanan, Perizinan, Kesejahteraan masyarakat